MICRONUTRIENT CONTENTS IN THE PROFILE OF A RECOVERED SOIL WITH SEWAGE SLUDGE AND NATIVE SPECIES OF ATLANTIC FOREST - Goulart, Lívia Mara Lima; Faria, Marianne Fidalgo de; Spada, Grasiela; Silva, Thiago Tássio de Souza; Guerrini, Iraê Amaral (Floresta, 2019)
The use of sewage sludge in agriculture and recovery of degraded areas has been shown as a promising alternative for its final destination. Studies on micronutrient levels after sludge application are necessary to avoid soil contamination at toxic levels. The objective of this work was to verify the micronutrient contents in the soil profile and pH, up to one-meter-deep, nine years after the application of sewage sludge and planting of native species of the Atlantic Forest. The experiment was implemented in a degraded Quartzeneic Neosol and conducted in randomized blocks with four replicates and eight treatments, consisting of six doses of sewage sludge (0, 2.5, 5, 10, 15 and 20 Mg ha-1, with supplementation of potassium due to low concentration in the residue), besides the control treatment, mineral fertilization and only potassium supplementation. After nine years, the contents of all micronutrients evaluated presented a significant response to the application of the treatments, and the application of sewage sludge provided an increase in their contents. Soil pH remained stable at sites receiving mineral fertilization and potassium supplementation. Only manganese and zinc showed mobility in the soil profile. The application of sewage sludge in degraded soil increases the micronutrient content and decreases its movement in the soil profile, and the application of the maximum dose of the residue does not provide toxic levels of these elements in the soil in the long term.